Administrative Views on Pedagogical Tolerance in Higher Education - Zhaniyat Baltabayeva; Sandugash Baisarina; Baizhuman Kashkhynbay; Miray Doğan (Üniversite Araştırmaları Dergisi)
For individuals to live together in society, they must comply with essential elements such as tolerance, respect and solidarity. Tolerance is respecting and understanding individuals’ ideas, feelings, and behaviors. For this reason, tolerance also plays a vital role for administrators in higher education. Pedagogical tolerance is the ability to accept and appreciate experiences, cultures and different perspectives in education, which is necessary to create inclusive, supportive learning environments. There are various studies on pedagogical tolerance. This study investigates the critical qualities required for sustainable and effective university leadership based on the responses of 26 participants from a university in Astana, Kazakhstan, to open-ended questions about pedagogical tolerance. The participants work in the positions of faculty deans, faculty department heads, and department administrative managers. The research was conducted using a qualitative research design. The answers to the open-ended questions asked of the participants were determined through content analysis. The research findings show that effective communication, cultural behavior, and emotional intelligence are essential for deans, as well as intelligence, respect, and responsibility for department heads. Strategic thinking, honesty, and technological literacy are emphasized for departmental administrators. Participants emphasize that having open-mindedness, empathy, and patience are essential in providing fair and quality education. Pedagogical tolerance is considered very important for ensuring sustainable education. In this context, it is recommended that seminars and training programs be organized for deans, faculty department heads and department managers. These trainings will enable them to understand better and apply pedagogical tolerance. These initiatives will provide comprehensive development opportunities for educational leaders in Kazakhstan and enable them to become competent in creating inclusive, respectful and supportive learning environments.